Coptotermes sp. (Rhinotermitidae: Coptotermitinae) infestation pattern shifts through time in oil palm agroecosystem - Nur-Atiqah J.,; Andi Saputra,; Mohammad Faris Mohammad Esa,; Shafuraa O.,; Annie Nunis Anak Billy,; Nurul Amalina Akmal Mohd Yaziz,; Faszly R., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Status of termite pest infestation as well as the changes through time, corresponding to oil palm conversion from peat in Malaysia can be studied. In accessing the status of palms infested by Coptotermes sp., stand scouting method was conducted to map the presence of this genus as well as the infestation status in each palm. The palms were accessed from ground level to hand-reached level and this was done in 24 ha field block with deep peat soil. The presence of Coptotermes sp., dead and replaced palms were recorded on census sheet, designed according to the real ground arrangement of the palms. Advanced spatial pattern by distance indices (SADIE) was adapted to generate the indices of aggregation and clustering values for each study sites. These values were exported into SURFER 8 software to generate red-blue contour maps with patches and gaps. Standardized stand scouting method yielded in six Coptotermes species collected in peat swamp converted oil palm field. The distribution pattern of Coptotermes caused by the environmental influences as well as the availability of wood resources. The patch and gap areas as well as the random areas are not consistently occurred. Small patches divided by gaps indicate one termite colony while larger patches are formed by more than one colony. This study contributes in the information on spatial pattern of termite pest species in oil palm plantation. The latter may present the changes in the status of the species over time.